Torsional dynamic response of a floating pile in radially inhomogeneous saturated soils - Hiep Toan Luong; Hien Manh Nghiem (Soils and Foundations, 2025)
The pile construction process may disturb the soil adjacent to the pile shaft that significantly influences the torsional dynamic response of the floating pile. To consider this problem, the disturbed soil is divided into series of annular zones and a varying-parameter dimensionless function represents the tangential displacement in the radial direction is proposed. The energy principles and variational approach are employed to establish the governing equations of the pile-soil system subjected to dynamic torque applied at the pile head in the frequency domain. The proposed method has the capability to consider the radially inhomogeneous soil as well as the soil behavior beneath the pile base and the vertical shear strain that were ignored or not fully accounted in the existing solutions. The accuracy of this approach is also verified through comparisons of analysis results with those of established analytical solutions. Parametric studies are also performed to investigate the influence of the soil properties and the excitation frequencies on the pile head dynamic stiffness and damping of the pile-soil system.